(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aimed at identifying the level of administrative work quality of private Schools principals at Southern Governorates of Palestine from the teachers’ point of view in their schools. To achieve the objectives of this research, a questionnaire was prepared by the researcher consisted of (28) items. It was applied to a sample of (350) teachers. The researcher adopted the descriptive-analytical approach. The results of the study showed that the degree to which principals of private schools in the southern governorates of Palestine practice Administrative Work Quality from the viewpoint of their teachers was very high, with relative weight (85.00%). The results also showed that there are statistically significant differences at the level of significance (a ≤0.05) between the estimated averages of the study sample in terms of gender in favor of females. Moreover, there are no statistically significant differences at the level of significance (a ≤0.05) between the estimated averages of the study participants due to the variables (educational qualification, years of service). The researcher recommended involving teachers, students, and the community in planning quality in schools, implementing programs to care for students with special needs (talented, poor attainment), and implementing preventive and therapeutic programs for students with behavioral and psychological problems in cooperation with the school’s educational guide.